2021
DOI: 10.1177/00469580211005188
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication Practice and Associated Factors among Private Health Sciences Students in Gondar Town, North West Ethiopia. A Cross-sectional Study

Abstract: Self-medication is the most common practice worldwide and it may lead to irrational use of drugs. Therefore, this study aimed to assess the prevalence of self-medication practice and its associated factors among health science students. A cross-sectional study was conducted on 600 health science students in Gondar town. The data regarding self-medication practice and its associated factors were collected using a face-to-face interview on a structured questionnaire. SPSS −24 was used for data analysis and expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 49 publications
4
27
1
1
Order By: Relevance
“…This was in contrast to a similar study in Nigeria which reported that Christians were more likely to self-medicate. 25 Among health sciences students in Ethiopia, both being Muslim and Protestant (Anglican) were significantly associated with self-medication 26 and similar findings have been reported among pregnant women in Ethiopia. 27 While it is challenging to find plausible explanations for this consistent finding, a qualitative study may provide an insight on how the various religious practices influence health-seeking behaviour, particularly self-medication.…”
Section: Discussionsupporting
confidence: 65%
“…This was in contrast to a similar study in Nigeria which reported that Christians were more likely to self-medicate. 25 Among health sciences students in Ethiopia, both being Muslim and Protestant (Anglican) were significantly associated with self-medication 26 and similar findings have been reported among pregnant women in Ethiopia. 27 While it is challenging to find plausible explanations for this consistent finding, a qualitative study may provide an insight on how the various religious practices influence health-seeking behaviour, particularly self-medication.…”
Section: Discussionsupporting
confidence: 65%
“…This has been defined by the WHO and included in one of the significant concerns in both developing and developed countries as indicated by various studies, especially in the wake of COVID-19 [ 21 , 22 ]. In the wake of social media becoming more accessible than the healthcare itself, misinformation regarding medication, pathophysiology of the disease, treatment, and prevention has led to public confusion and panic [ 23 ]. It has been documented that along with an ongoing pandemic, there have been several small endemic diseases like mucormycosis, and an equally disturbing infodemic going on in the world [ [24] , [25] , [26] ].…”
Section: Otc Drug Abuse In India During the Covid-19 Pandemicmentioning
confidence: 99%
“…However, fear, the saturation of hospitals and the economic impact of the COVID-19 pandemic 5 has encouraged us to carry out this practice more frequently and even increased the prevalence in the young population 6 . Since they justified the practice by diverse factors among them; 33.49% of the young people relate the similarity of the symptoms to past illnesses, 19.17% perceived the illness as something mild, and 18.24%, from the economic aspect, self-medication was cheaper for them 7 . In addition, in Peru, at the beginning of the pandemic, kits were distributed to treat mild coronavirus disease; Therefore, when some were hospitalized for the disease, they reported having self-medicated with ivermectin that they had given to their relatives 8 .…”
Section: Editorialmentioning
confidence: 99%
“…Sin embargo, el miedo, la saturación de hospitales y la afectación económica por la pandemia COVID-19 5 ha incentivado a realizar con más frecuencia esta práctica e inclusive aumentó la prevalencia en la población joven 6 . Puesto que, justificaban la práctica por diversos factores entre ellos; el 33,49 % de los jóvenes relacionan la similitud de los síntomas con enfermedades pasadas, el 19,17 % percibían la enfermedad como algo leve, el 18,24 % desde el aspecto económico les resultaba más barato la automedicación 7 . Además, en Perú, al inicio de la pandemia se distribuyó kits para tratar la enfermedad leve por coronavirus; por lo que algunos cuando eran hospitalizados por la enfermedad, referían haberse automedicado con ivermectina que les habían entregado a sus familiares 8 .…”
unclassified